Molecular characterization of homogentisate phytyltransferase and methylphytylbenzoquinol methyltransferase genes from olive fruit with regard to the tocopherol content and the response to abiotic stresses - Narváez, Isabel; Hernández, M. Luisa; Sicardo, M. Dolores; Velázquez-Palmero, David; Moreda, Wenceslao; Martínez-Rivas, José M. (Frontiers in Plant Science, 2025)
Two cDNA sequences, named OepHPT and OepMPBQ MT, encoding homogentisate phytyltransferase (HPT) and methylphytylbenzoquinol methyltransferase (MPBQ MT), respectively, have been cloned from olive (Olea europaea cv. Picual). Sequence analysis displayed the distinguishing characteristics typical of the HPT and MPBQ MT families and along with phylogenetic analysis indicated that they code for homogentisate phytyltransferase and methylphytylbenzoquinol methyltransferase enzymes, respectively. Transcriptional analysis in distinct olive tissues indicated that expression levels of HPT and MPBQ MT genes are spatially and temporally regulated in a cultivar-dependent manner and together with tocopherol analysis pointed out that both genes participate in the biosynthesis of the tocopherols present in olive mesocarp. These data also suggest that in olive mesocarp, HPT but not MPBQ MT could be implicated in the transcriptional regulation of the tocopherol biosynthetic pathway. In addition, HPT and MPBQ MT transcript levels are regulated by water status, temperature, light, and wounding in the olive fruit mesocarp, suggesting that both genes could be implicated in the abiotic stress response. Overall, this research constitutes a significant advance to elucidate the factors that regulate the tocopherol biosynthesis in olive fruit to obtain virgin olive oils with enhanced α-tocopherol content.